2020
DOI: 10.1371/journal.pntd.0008615
|View full text |Cite
|
Sign up to set email alerts
|

The Aedes albopictus (Diptera: Culicidae) microbiome varies spatially and with Ascogregarine infection

Abstract: The mosquito microbiome alters the physiological traits of medically important mosquitoes, which can scale to impact how mosquito populations sustain disease transmission. The mosquito microbiome varies significantly within individual mosquitoes and among populations, however the ecological and environmental factors that contribute to this variation are poorly understood. To further understand the factors that influence variation and diversity of the mosquito microbiome, we conducted a survey of the bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…Burkholderiaceae were previously found to be associated with Ae. albopictus breeding sites ( Shelomi, 2019 ) as well as adults ( Seabourn et al, 2020 ). Similarly, larval and pupal samples from Ae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Burkholderiaceae were previously found to be associated with Ae. albopictus breeding sites ( Shelomi, 2019 ) as well as adults ( Seabourn et al, 2020 ). Similarly, larval and pupal samples from Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Individual adults were also used to obtain data related to Wolbachia infection at the single-mosquito level. Prior to DNA extraction from both larval pools and adults, each individual was surface-washed twice with 1X PBS, after washing in ethanol 70% (following Seabourn et al, 2020 ). DNA extraction was performed using the Wizard Genomic DNA Purification Kit (Promega) following the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The diversity of midgut microbiota has been studied and identified from various species of mosquitoes, primarily Anopheles mosquitoes ( Tainchum et al., 2020 ; Zoure et al., 2020 ). In contrast, studies of Aedes and Culex mosquitoes are limited ( Tiawsirisup et al., 2018 ; Muturi et al., 2020 ; Seabourn et al., 2020 ). In the present study, we examined the diversity of midgut bacteria in female laboratory-colonized and field-collected Ae.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been known that the composition of Ae. albopictus microbiome varies between individuals, populations, even between field and colony mosquitoes ( Seabournid et al, 2020 ); some studies have shown that 24–48 h after a blood meal, bacterial abundance increases, but diversity decreases ( Wang et al, 2011 ; Terenius et al, 2012 ). In this study, we found that 6 h after blood-feeding the activity of Actinobacteria, Rhodospirillaceae, and Anaplasmataceae increase significantly.…”
Section: Discussionmentioning
confidence: 99%
“…Although the microbiome of mosquitoes can be highly variable, both within and between species, it is often dominated by relatively few genera. For mosquitoes, microbiota-host interactions can influence a diverse number of physiological traits including immunity, reproduction, survival, and vector competence ( Scolari et al, 2019 ; Seabournid et al, 2020 ). Due to this effect, the interest in mosquitoes microbiome manipulation to control the transmission of vector borne diseases has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%